Personal Financial Management Practices of Average earning households within Indigenous Communities of Mountain Province: Exploring Their Strategies and Challenges - Rosario, Elvin P. (Journal of Cultural Analysis and Social Change, 2025)
This study examined the financial management practices, challenges, and coping mechanisms of average-earning households in Bontoc, Mountain Province, within the context of cultural traditions and socioeconomic realities. Guided by a qualitative design, the research gathered insights from participants belonging to households across different barangays of Bontoc and applied thematic analysis supported by relevant financial management theories. Findings revealed that households face persistent financial challenges such as income insufficiency, rising costs of basic goods, and obligations to education, healthcare, and cultural traditions. To address these, families employed strategies including strict budgeting, sideline work, borrowing, and reliance on extended kinship networks. Financial stress was found to manifest in psychological strain, disrupted education of children, and limited healthcare access. Nonetheless, coping mechanisms reflected both modern financial literacy practices such as budgeting, savings, and diversification, and indigenous cultural practices including og-ogfo and bayanihan. These combined strategies highlight the integration of economic, social, and cultural resilience in household financial life. The study concludes that sustainable household financial management in Bontoc cannot be addressed solely by modern financial frameworks; it must also recognize indigenous practices that strengthen community solidarity. It recommends policy interventions to enhance income stability, improve access to education and healthcare, and promote culturally sensitive financial literacy programs.